Pengaruh e-WOM (Electronic Word of Mouth) Terhadap Keputusan Pembelian online di Daerah Istimewa Yogyakarta - Hardoko Hardoko (Jurnal Solusi, 2020)
Transactions with internet media in Indonesia have experienced rapid growth along with the increasing use of the internet in Indonesia. In 2018 internet users in Indonesia reached 171.17 million users, or 64.8% of the population of Indonesia. Of these, 96% of internet users in Indonesia have made transactions with internet media. Word of mouth communication is transformed into E-WOM (electronic word of mouth) along with the development of internet technology at this time. The purpose of this study is to analyze the dimensions of e-Wom, namely the effect of intensity (intensity), valence of opinion (content of opinion) and content (content) on online purchasing decisions in the Special Region of Yogyakarta. The sampling method used in this study was non-probability sampling using purposive sampling technique for a sample of 100 respondents scattered in Sleman, Yogyakarta, Bantul, Kulonprogo and Gunungkidul. Data analysis in this research uses Multiple Linear Regression. The results of this study indicate that valence of opinion and content are variables that have a positive and significant influence on online purchasing decisions in the Special Region of Yogyakarta. While the intensity variable has a positive but not significant effect on online purchasing decisions in the Special Region of Yogyakarta. 24.6% of online purchasing decisions in the Special Region of Yogyakarta are influenced jointly by intensity, valence of opinion and content, the rest by other reasons